Clinical characteristics and prognosis of 196 Chinese patients with colon cancer - Yao, Lunjin; Zhang, Huihui; Wang, Weipeng; An, Xiaoxia; Cheng, Zhiqiang; Zhang, Xiang; Wang, Kexin; Zhang, Binbin (Frontiers in Surgery, 2023)
AIMS: To analyze the clinical characteristics and prognostic factors of Chinese patients with colon cancer. METHODS: A retrospective analysis of the records of patients with colon cancer underwent surgery between 2014 and 2017 was performed. Univariate analysis in combination with Cox proportional hazard regression model was used to analyze the survival data, so as to reveal the prognostic factors of colon cancer. Data record was based on a standard data form. SPSS version 26.0 was used for data analysis (SPSS, Chicago, IL, United States). RESULTS: The 3-year survival rate and the 5-year survival rate was 79.3% and 68.2%, respectively. Univariate analysis showed that radical surgery, laparoscopic surgery, ascites, swollen lymph nodes at the root of the mesentery, liver metastases, nerve invasion, vascular invasion, tumor node metastasis (TNM) staging, positive level of carbohydrate antigen (CA) 19-9, CA125, CA72-4 and combined detection were positive factors in the prognosis of colon cancer(P<0.05). Multivariate analysis showed that radical surgery and TNM staging were independent factors affecting the prognosis of patients with colon cancer(P<0.05). CONCLUSION: Radical surgery and TNM staging have a significant impact on the prognosis of patients with colon cancer.